New Evidence on News-Driven Business Cycles - Thomas Haertel; Bernd Lucke (Kiel Institute for the World Economy (IfW), 2007)
We study the Beaudry and Portier (2006)-hypothesis of delayed-technology diffusion and newsdriven business cycles. For German data on TFP and stock prices we find qualitatively similar empirical evidence. Quantitatively, however, an impulse response analysis suggests that a substantial part of the total TFP response is immediate rather than delayed. We relate this to disembodied technological change and noisy data on TFP. Nevertheless, we confirm the technology interpretation of structural shocks by showing that they are Granger-causal for data on patents granted by the German patent agency.
Keywords: E32; 330; news; business cycles; TFP; structural VAR